Development of Coir-fibre Cement Composite Roofing Tiles. (2016) - Darsana, P.; Abraham, Ruby; Joseph, Anu; Jasheela, Arakkal; Binuraj, P.R.; Sarma, Jithin
Abstract: In order to optimize the cost of construction, engineers have always been on the lookout for efficient and light roofing which requires minimum maintenance and labor to install. Coir is a green building material and has potential as a raw material for the production of roofing materials like corrugated sheets and tiles. The main objective of the paper is to produce cost effective roofing tiles without compromising their quality by replacing cement up to 15% using coir fibre. On the basis of the results, a composite with a fibre volume of 10% was considered to be the optimum composite. A comparison of material costs indicated that this composite tile was substantially cheaper than the ordinary cement concrete tile.